Determination of glandular tissue thickness in film - Rodríguez-Jirón, Marco A. (2023)
A method to determine the relationship between film optical density and the thickness of glandular breast tissue using materials available in developing countries was developed. A phantom was created using acrylic slabs. The slabs were cleaned to remove all residues from the acrylic surfaces before usage. The phantom was designed in a staircase-shape array with varying step heights. The correlation between acrylic height, breast tissue thickness, and optical density was studied by measuring the optical density at points corresponding to different acrylic heights. The phantom images were captured on a Kodak Mammography film using a 20 keV Mo/Mo x ray source with an RQR8 filter. The optical density at each point of interest was measured using a PTW densitometer. It was found that the optical density decreased exponentially with acrylic height. The maximum error observed for our imaging system was below 1% across all thicknesses investigated. The proposed phantom design offers a means to determine the relationship between optical density and the thickness of glandular breast tissue.